Protective Effects of Inflammation of Curcumae Longae Rhizoma 30% EtOH Extract on Acute Reflux Esophagitis Rats. (18th January 2021) - Lee, Jin A.; Shin, Mi-Rae; Kim, Min Ju; Lee, Ji Hye; Park, Hae-Jin; Roh, Seong-Soo
Abstract : Gastroesophageal reflux disease (GERD) is induced by the reflux of stomach contents or gastric acid, pepsin into the esophagus for prolonged periods of time due to defection of the lower esophageal sphincter. Reflux esophagitis is a disease found in less than 50% of GERD patients. This study is aimed at evaluating the protective effect of Curcumae longae Rhizoma 30% EtOH extract (CLR) in acute reflux esophagitis (ARE) rats. CLR measured antioxidant activity through in vitro experiments. Based on the results, we performed experiments in vivo . Before 90 min ARE induction, CLR was administered orally by concentration. ARE was derived by linking the metastatic junction between pylorus and forestomach and corpus in Sprague-Dawley rats. And rats were sacrificed 5 h after surgery. We analyzed the expression of antioxidant and inflammatory-related markers by western blot and observed the production of alanine aminotransferase (ALT), aspartate aminotransferase (AST), reactive oxygen species (ROS), peroxynitrite (ONOO - ), and thiobarbituric acid reactive substance (TBARS). The administration of CLR reduced esophagus tissue damage in rats with acute reflux esophagitis and decreased the elevated ALT, AST, ROS, ONOO -, and TBARS. In addition, CLR effectively increased antioxidant-related factors and reduced inflammatory protein. Overall, these results suggest that CLR would be used as a therapeutic material in protection and treatment for ARE. Overall, CLR treatment informed that markedly ameliorated inactivation of NF- κ B led to the inhibition of the expressions of proinflammatory proteins. These results suggest that CLR would be used as a therapeutic material in protection and treatment for ARE.